2009
DOI: 10.1073/pnas.0810427106
|View full text |Cite
|
Sign up to set email alerts
|

Tissue destruction caused by cytotoxic T lymphocytes induces deletional tolerance

Abstract: Autoimmune diseases tend to be chronic and progressive, but how these responses are sustained is not clear. One cell type that might contribute to autoimmunity is the cytotoxic T lymphocyte (CTL), which, as a consequence of causing tissue destruction and production of cytokines, could provide a sustained supply of antigen and inflammatory signals for dendritic cells to maintain immune stimulation. Here we examined whether such CTL-mediated tissue damage alone could provide antigen in the right context to recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
3
22
1
Order By: Relevance
“…To experimentally prove whether this state of self-tolerance could be broken by the combined Foxp3 + Treg depletion plus vaccination protocol, we crossed DEREG mice with RipOVA low mice (26) expressing OVA as neoself-antigen under control of the rat insulin promoter. It has been previously shown that transfer of OVA-specific CTL in RipOVA low mice results in the destruction of pancreatic islets and diabetes onset (46). In untreated DEREG × RipOVA low mice, we observed a rapid growth of B16-OVA melanoma, reaching a mean tumor diameter of 10 to 12 mm within 2 weeks (Fig.…”
Section: Combining Selective Foxp3mentioning
confidence: 59%
“…To experimentally prove whether this state of self-tolerance could be broken by the combined Foxp3 + Treg depletion plus vaccination protocol, we crossed DEREG mice with RipOVA low mice (26) expressing OVA as neoself-antigen under control of the rat insulin promoter. It has been previously shown that transfer of OVA-specific CTL in RipOVA low mice results in the destruction of pancreatic islets and diabetes onset (46). In untreated DEREG × RipOVA low mice, we observed a rapid growth of B16-OVA melanoma, reaching a mean tumor diameter of 10 to 12 mm within 2 weeks (Fig.…”
Section: Combining Selective Foxp3mentioning
confidence: 59%
“…Mice in which Em-myc-GFP or Em-myc-OVA tumors (FSC high B220 int GFP + ) had been growing for 3-5 d were treated with anti-OVA OT-I CTLs generated in vitro (22) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro activation of OT-I and gBT-I ) or gBT-I cells were generated as described (22). Cultures typically contained 94-98% CD8 + Va2 + cells.…”
Section: Em-myc Lymphomasmentioning
confidence: 99%
“…This is based on studies in mice expressing ovalbumin under the control of the rat insulin promoter, wherein pancreatic tissue destruction was initiated by transfer of OVA-specific CD8 effector T cells (OT-1 cells) (15). The authors found that naïve OT-I T cells underwent deletional tolerance when encountering OVA liberated and cross-presented in draining lymph nodes of these mice (15). However, pancreas destruction resolved without overt autoimmune disease (15).…”
Section: Introductionmentioning
confidence: 99%